The relation between stretching typology and stretching duration: The effects on range of motion - Thomas, E.; Bianco, A.; Paoli, A.; Palma, A. (International Journal of Sports Medicine, 2018)
Different stretching strategies and protocols are widely used to improve flexibility or maintain health, acting on the muscle tendon-unit, in order to improve the range of motion (ROM) of the joints. This review aims to evaluate the current body of literature in order to understand the relation between stretching typology and ROM, and secondly to evaluate if a relation exists between stretching volume (either as a single training session, weekly training and weekly frequency) and ROM, after long-term stretching. Twenty-three articles were considered eligible and included in the quantitative synthesis. All stretching typologies showed ROM improvements over a long-term period, however the static protocols showed significant gains (p<0.05) when compared to the ballistic or PNF protocols. Time spent stretching per week seems fundamental to elicit range of movement improvements when stretches are applied for at least or more than 5min, whereas the time spent stretching within a single session does not seem to have significant effects for ROM gains. Weekly frequency is positively associated to ROM. Evaluated data indicates that performing stretching at least 5 days a week for at least 5min per week using static stretching may be beneficial to promote ROM improvements.